Improved oil recovery by reducing surfactant adsorption with polyelectrolyte in high saline brine - Budhathoki, M. (Elsevier B.V., 2016)
Surfactant adsorption on reservoir rock is one of the biggest challenges of chemical enhanced oil recovery (cEOR) techniques. This problem can become severe in high saline brine environments. In this work, the efficacy of a polyelectrolyte, polystyrene sulfonate (PSS), as a sacrificial agent for lowering surfactant adsorption from reservoir brine that has totally dissolved solids (TDS) of over 300,000 mg/l is investigated. Four different molecular weight PSSs are evaluated through equilibrium and dynamic adsorption studies carried out on Berea sandstone and Ottawa sand. Results show significant reduction in surfactant adsorption after PSSs addition. The effects of surfactant/PSS addition techniques, sequential and simultaneous, on surfactant and/or PSS adsorptions are also studied. Sand pack studies are conducted to evaluate the effect of PSS-minimized surfactant adsorption on oil mobilization/recovery. Results show substantial improvement in oil recovery in the presence of PSS, suggesting a potential as a sacrificial agent in cEOR. Â© 2016 Elsevier B.V.